The Effect of Beta, Price to Book Value, Company Size, Profitability and Investment on Stock Returns - Agustina Marsella Klau Seran; Dewa Gede Wirama (Institut Teknologi dan Bisnis (ITB) Semarang, 2025)
This study aims to obtain empirical evidence regarding the influence of 5 factors in the Fama-French 5 Factor Model, namely beta, price to book value , company size, profitability and investment on stock returns. This study analyzed 270 samples of companies listed on the Indonesia Stock Exchange for the 2022 period. The samples were selected using the probability sampling method and analyzed using multiple linear regression analysis techniques. The results of the study indicate that beta and investment have a positive effect on stock returns, company size has a negative effect on stock returns, but price to book value and profitability have no effect on stock returns. The results of this study are not fully able to confirm the accuracy of the Fama-French 5 Factor Model.